Estimation of efficiency of the differentiated program of physical education of the special educational separation with the use of facilities of the health walking and at run for students with a vascular dystonia - Gatsko E.V (Kharkov National Pedagogical University, 2010)
The differentiated program of the health walking and at run is examined. 70 students took part in pedagogical research. Students are up-diffused on two groups (20 and 30 students) and the III group (20 students) is practically healthy. All students are in age of 17-20 years. It is set that regular and long employments walking and running promote functional possibilities of organism and level of physical capacity. At the increase of degree of trained functional expenses diminished on implementation of the physical loading.